Pendekatan Psikologi Islam dan Barat dalam Memahami Hakikat Manusia: Analisis Kualitatif tentang Konsep Jiwa dan Kepribadian - Ane Zunnatul Mafruhah; Yanti Amalia Afifah; Aris Rahman Saleh; Isop Syafe’i; Izzuddin Musthafa; Muhammad Chafidz Ali Wafa (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study aims to analyze the concept of human nature from the perspectives of Western and Islamic psychology and to explore its relevance to contemporary personality theory. The research employs a descriptive qualitative method with a library research approach, using Manahij At-Tarbiyah Fii At-Tashawwur Al-Islamiy by Ali Ahmad Madkur as the primary source, along with supporting literature from Western and Islamic psychology. The findings reveal that Western psychology, through psychoanalytic, humanistic, and behavioristic approaches, views humans as rational and biological beings whose behavior is shaped by drives, experiences, and environmental factors. In contrast, Islamic psychology perceives humans as spiritual beings composed of the soul (an-nafs), intellect (al-‘aql), and heart (al-qalb), which interact under divine guidance. The discussion indicates that Western psychology emphasizes rational, biological, and social aspects, while Islamic psychology integrates spiritual, moral, and rational dimensions. Although both aim to understand human wholeness, they differ in epistemological foundations and moral orientations. Ali Ahmad Madkur’s thought offers an integrative paradigm that unites spirituality, intellect, and morality as the foundation for understanding human personality comprehensively. Thus, his perspective makes a significant contribution to modern psychology by integrating Islamic values with psychological science, providing a holistic understanding of the human being as a spiritual, rational, and moral entity.